Economic Valuation of Recreational Fishing in Western Australia: Statewide Random Utility Modelling of Fishing Site Choice Behaviour - Raguragavan, Jananee; Hailu, A.; Burton, M. (Blackwell Publishing Asia, 2013)
Allocation of fish resources is a controversial subject. This is partly because of our limited understanding of the values of fishing opportunities. This study investigates fishing site choices in Western Australia using national survey data covering eight major fishing regions and forty-eight fishing sites. We estimate a random utility model (RUM) of site choice with a supporting negative binomial model of angler-specific expected catch rates. Value estimates for fish types, fishing site attribute changes and access values are presented and discussed.